2009
DOI: 10.1063/1.3266763
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Children’s Understanding And Interest In Science Through Informal Science Education

Abstract: Abstract. We present results from the University of Colorado's Partnership for Informal Science Education in the Community (PISEC) in which university participants work in afterschool programs on inquiry-based activities with primary school children from populations typically under represented in science. This university-community partnership is designed to positively impact youth, university students, and the institutions that support them while improving children's attitudes towards and understanding of scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
13
0
2
Order By: Relevance
“…A few activities incorporated more student-structured investigations (see Discussion); however, these questions were located toward the end of the curriculum and most students did not have enough time to complete more than one of these activities. Based on observations and pre/post test analysis, by the end of the semester students were able to correctly build, identify and explain circuit configurations that would cause single bulbs to light, an outcome shown in prior semesters [7]. While content learning was evident, the students, teachers and volunteers reported that the program was not very engaging and expressed a desire to do more hands-on experiments.…”
Section: Inquiry Curriculamentioning
confidence: 94%
“…A few activities incorporated more student-structured investigations (see Discussion); however, these questions were located toward the end of the curriculum and most students did not have enough time to complete more than one of these activities. Based on observations and pre/post test analysis, by the end of the semester students were able to correctly build, identify and explain circuit configurations that would cause single bulbs to light, an outcome shown in prior semesters [7]. While content learning was evident, the students, teachers and volunteers reported that the program was not very engaging and expressed a desire to do more hands-on experiments.…”
Section: Inquiry Curriculamentioning
confidence: 94%
“…Bu anlamda çeşitli sosyobilimsel konuların okul dışı öğrenme ortamlarında işlenmesiyle bu konulara dayalı öğrenmeler gerçekleşebilir. Bu bulgulara paralel şekilde literatürde okul dışı öğrenme ortamlarının öğrencilerin farkındalık ve bilgi düzeylerindeki değişimi (Bartley, Mayhew ve Finkelstein, 2009;Fisman, 2005;Pereira ve diğerleri, 2006;Randler ve diğerleri, 2012;Sanders, 2007), öğrenmelerini (Bätz, Wittler ve Wilde 2010;Tosun, 2012), kavramları anlama düzeylerindeki değişimi (Sağlamer Yazgan, 2013) olumlu yönde etkilediğini vurgulayan çalışmalar yer almaktadır. Ayrıca sosyobilimsel tartışma destekli öğretimin öğrencilerin bilgi düzeylerindeki değişimi (Şahintürk, 2014;Taşpınar, 2011) ve sosyobilimsel aktivitelerle verilen eğitimin kavram öğrenmelerini (Goloğlu, 2009) olumlu yönde etkilediğini inceleyen çalışmalara rastlanmıştır.…”
Section: Tartışma / Sonuç Ve öNerilerunclassified
“…Some pedagogies that we use, either in a regular or flipped classroom setting, include group work, peer instruction [5][6][7] (including using personal response systems or clickers [6]), problem/project based learning (PBL, for example see [10]), reflective writing exercises [11], computer/ICT based activities [12][13][14][15][16], incorporating creativity [17][18] and learning outside of the classroom (i.e. class outings) [19].…”
Section: The Quebec College System and Its Physics Classroommentioning
confidence: 99%